On oscilation and asymptotic behaviour of solutions of one system of differential-functional equations of neutral type - Ivanov , A. F.; Marushiyak , P. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Conditions for the oscillation of all solutions and for the existence of nonoscillatory solutions with polynomial growth at infinity are given for the system of differential-functional equations of neutral type\(\frac{{d^n }}{{dt^n }}[x(t) + \lambda _1 x(t - \tau _1 )] = p(t)f(y(\theta _1 (f)), \\ \frac{{d^n }}{{dt^n }}[y(t) + \lambda _2 y(t - \tau _2 )]q = (t)g(x(\theta _2 (t)),  \\ 0 \leqslant |\lambda _1 |,|\lambda _2 |< 1. \)